Natural Killer Cells: Potential Biomarkers and Therapeutic Target in Autoimmune Diseases? - Gianchecchi, Elena; Delfino, Domenico V.; Fierabracci, Alessandra (Frontiers in Immunology, 2021)
Autoimmune diseases recognize a multi-factorial pathogenesis although the exact mechanism responsible for their onset remains to be fully elucidated. During the last years, the role of NK cells in shaping immune responses has been highlighted, even though their involvement is profoundly linked to the subpopulation involved as well as to the site where such interaction takes place. Aberrant number and functionality of NK cells have been reported in several different autoimmune disorders. In the present review, we report the most recent findings regarding the involvement of NK cells in both systemic and organ-specific autoimmune diseases including type 1 diabetes, primary biliary cholangitis, systemic sclerosis, systemic lupus erythematosus (SLE), primary Sjögren’s syndrome, rheumatoid arthritis and multiple sclerosis (MS). In type 1 diabetes (T1D) innate inflammation induces NK cell activation disrupting Treg function. In addition, certain genetic variants identified as risk factors for T1D influenced the activation of NK cells promoting their cytotoxic activity. The role of NK cells has been demonstrated also in the pathogenesis of primary biliary cholangitis mediating direct or indirect biliary epithelial cell destruction. NK cell frequency and number were enhanced in both peripheral blood and livers of patients, and associated with increased NK cell cytotoxic activity and perforin expression levels. NK cells were also involved in the perpetuation of disease through autoreactive CD4 T cell activation in presence of antigen presenting cells. Concerning Systemic sclerosis (SSc), beside to phenotypic abnormalities, patients presented a reduction in CD56hi NK‐cells. Moreover, NK cells presented a deficient killing activity. The influence of the activating and inhibitory Killer-cell Immunoglobulin-like Receptors (KIRs) has been investigated in SSc and SLE susceptibility. Furthermore, autoantibodies to KIRs have been identified in different systemic autoimmune conditions. Due to its role in modulating the immune-mediated pathology, NK subpopulation could represent a potential marker for disease activity and target for therapeutic intervention.